Catalytic dehydration of lactic acid to acrylic acid using calcium hydroxyapatite catalysts - Ghantani, Vidhya C.; Lomate, Samadhan T.; Dongare, Mohan K.; Shubhangi B. Umbarkar (Green Chemistry, 2013)
A series of calcium hydroxyapatite (HAP) catalysts were synthesised with a Ca/P ratio ranging from 1.3 to 1.89 by a co-precipitation method that involved changing the pH of the calcium and phosphorous precursors. The physicochemical characterization by XRD, SEM, BET surface area and CO2 and NH3-TPD techniques confirmed the hydroxyapatite formation. These HAP catalysts were used for the vapour phase dehydration of lactic acid to acrylic acid. The HAP catalyst with a Ca/P ratio of 1.3 was found to be the most efficient catalyst among the synthesised series, which gave 100% conversion of lactic acid and 60% selectivity towards acrylic acid at 375 degrees C when a 50% (w/w) aqueous solution of lactic acid was used. The higher selectivity towards acrylic acid has been correlated to the increased acidity and reduced basicity of the HAP catalyst with a Ca/P ratio of 1.3 compared to the other HAP catalysts. The catalyst was found to be very stable and no deactivation was observed even after 300 h of reaction time. In situ FTIR studies were performed for understanding the mechanistic aspects and showed the formation of calcium lactate as an intermediate species during the dehydration of lactic acid to acrylic acid.

Nonstoichiometric calcium pyrophosphate: a highly efficient and selective catalyst for dehydration of lactic acid to acrylic acid - Ghantani, Vidhya C.; Dongare, Mohan K.; Shubhangi B. Umbarkar (RSC Advances, 2014)
Calcium phosphate catalysts were prepared by co-precipitation method using calcium nitrate and mixtures of ammonium and different sodium phosphates as calcium and phosphate precursors, respectively. Depending on the phosphate precursor, the pH of the synthesis mixture changed during the catalyst precipitation. The catalyst characterisation by XRD and ICP revealed the formation of a calcium pyrophosphate structure with varying Ca/P ratio from 1.02 to 0.76 which could be correlated to the different pH of the synthesis solutions. Vapour phase dehydration of lactic acid to acrylic acid was carried out using these calcium pyrophosphate catalysts. Non-stoichiometric calcium pyrophosphate catalyst with Ca/P ratio 0.76 was found to be the most efficient catalyst among the synthesized series with 100% lactic acid conversion and 78% acrylic acid selectivity at 375 degrees C. The higher selectivity for acrylic acid has been correlated to the increased acidity and reduced basicity of non-stoichiometric calcium pyrophosphate compared to other stoichiometric pyrophosphates. In situ FTIR studies showed the formation of a higher amount of calcium lactate on non-stoichiometric compared to stoichiometric pyrophosphate leading to higher selectivity for acrylic acid.